The Joint Effect of the Type of Stakeholder and Incentive on the Acceptance of Budgetary Slack. Observed Differences in the Hierarchy of Needs Indicated by Polish Management Accountants - Nowak, Marta; Maruszewska, Ewa Wanda (Połączony wpływ typu interesariusza oraz występowania zachęty na manipulacje w budżecie. Zaobserwowane różnice w hierarchii potrzeb wskazanych przez polskich specjalistów z zakresu rachunkowości zarządczej, 2022)
We aimed to investigate the joint effect of the type of incentive and stakeholder on the acceptance of budgetary slack and examine the rankings of the five needs in Maslow’s pyramid. Using experimental research we demonstrated that motivational incentive and type of stakeholder interacted to affect the acceptance of budgetary slack. Management accountants experiencing non-monetary incentives in a situation where internal stakeholders’ expectations can be met with budgetary slack, showed the highest acceptance of budgetary slack. Respondents not accepting budgetary slack as professional behaviour ranked higher the needs that are on the top of Maslow’s pyramid.
Financial Sciences. Nauki o Finansach, 2022, vol. 27, no. 1, s. 14-27
Keywords: budgetary slack; hierarchy of needs; Maslow; stakeholder theory; behavioural accounting; manipulacje w budżecie; hierarhia potrzeb; teoria interesariuszy; rachunkowość behawioralna